Multicomponent crystals of vanillic acid - Tshahwa, Célestine Nyingika (Cape Peninsula University of Technology, 2025)
Vanillic acid (VA) was used to form multicomponent crystals with 4,4-bipyridine (4,4-BP), 4- dimethylaminopyridine (4DMAP), 2-amino-5-methylpyridine (A25MP), 2-amino-6- methylpyridine (A26MP), 2-aminopyridine (A2MP) and 4-aminopyridine (A4MP). Six compounds were prepared using the slow evaporation technique comprising one cocrystal, three salts and two salt hydrates. The compounds were characterised using FTIR spectroscopy, thermal analysis and powder X-ray diffraction. Crystal structures were determined using single crystal X-ray diffraction. Some compounds were successfully prepared using the grinding procedure, while others were only partially converted. Thermogravimetry was used for the salt hydrates to obtain the percentage water contained in the crystal structures. Supramolecular interactions in the obtained crystal structures of the cocrystal, salts and salt hydrates are dominated by hydrogen bonding (O-H···O and O-H···N), whereas π-π stacking and C-H··· π interactions played a minor role in the packing arrangements of the new solid forms
Thesis (Master of Applied Science: Chemistry)--Cape Peninsula University of Technology, 2025